Synchronization of cyclic and acyclic embryo recipient mares with donor mares - Oliveira Neto, Ivan V. [UNESP]; Canisso, Igor F.; Segabinazzi, Lorenzo G. [UNESP]; Dell'Aqua, Camila P.F. [UNESP]; Alvarenga, Marco A. [UNESP]; Papa, Frederico O. [UNESP]; Dell'Aqua, Jose A. [UNESP] (Elsevier, 2018)
This study compared hormone treatments given to mares during anestrus, spring transition, and different stages of the estrous cycle, by assessing uterine features and pregnancy rates after embryo transfer (ET). Embryo recipient mares (n = 160) were equally arranged as follows: G1-spontaneous ovulation (control), G2-anestrus, G3-spring transition, G4-early estrus, G5-estrus, G6-diestrus, G7-early diestrus treated with a dose of dinoprost, and G8-early diestrus treated with two doses of dinoprost. At treatment initiation (Day-4), G2-7 were given dinoprost and estradiol-17β, thereafter, estradiol-17β was repeated on Days-3,-2, and -1. On Day0, mares received long-acting altrenogest. Then, each mare had one ET performed from Day + 3 to Day + 8 after altrenogest. Immediately before the ET, mares received a boost of altrenogest and had uterine features assessed. Pregnant mares on each of the checks (by 7, 30, 60, and 120d after ET) were maintained on weekly injections of LA-P4 until 120d. G8 received similar management, but dinoprost was repeated on Day-3. G1-G6 and G8 displayed uterine edema and satisfactory pregnancy rates ≥65%. Repeating dinoprost to G8 likely ensured proper luteolysis and response to estrogen as determined by higher uterine edema scores and pregnancy rates than G7 (p <.05). Our results were consistent with previous studies and other successful commercial ET programs (except G7), thus, demonstrating the usefulness of the hormone treatments described herein to synchronize embryo recipient mares with donor mares. Thus, we foresee that other groups may use the strategies described herein for the management of embryo recipient mares.
Keywords: Embryo transfer; Estrogen; Hormone therapy; Progestin; Uterine edema